The Impact of Indoor Plants on Patient Recovery: Physiological and Psychological Effects in Dental Clinics - Mohamed Elsadek; Junfang Xie; Gao Jie (HortScience, 2023)
Patient recovery and well-being in healthcare settings can be influenced by various factors, including the stress induced by hospitalization and medical care. This study investigated the impact of indoor plants on patient recovery in dental clinics using state-of-the-art techniques to address the limited evidence supporting the claim that nature can alleviate stress and pain in hospitals. Thirty patients were randomly assigned to either a room with indoor plants or a control room without plants for a duration of 5 minutes after their treatment. Physiological responses were assessed using electroencephalography (EEG), heart rate variability, and skin conductance, whereas psychological responses were evaluated using the State-Trait Anxiety Inventory (STAI) and a visual analogue scale (VAS). The results revealed a significant increase in alpha wave power in the frontal region, indicating enhanced relaxation, as well as a significant increase in parasympathetic activity, suggesting improved autonomic balance. Furthermore, a significant decrease in skin conductance was observed when indoor plants were present compared with their absence, indicating reduced physiological arousal. Psychological assessments using the STAI demonstrated lower levels of stress and anxiety, whereas the VAS indicated reduced pain intensity among participants. Overall, these findings suggest that the presence of indoor plants contributes to patients’ relaxation and improved coping mechanisms during the recovery process. This study highlights the significance of incorporating indoor plants into healthcare settings to enhance patients’ overall well-being and promote positive recovery outcomes.